Acute kidney injury in asphyxiated neonates - Roy Amardiyanto; Partini Pudjiastuti Trihono; Lily Rundjan; Hardiono D. Pusponegoro (Paediatrica Indonesiana, 2013)
Background Asphyxia neonatorum may result in multiorgandysfunction including renal involvement. There is no consensuson the determination of acute kidney injury (AKI) in neonatesmaking establishment of the diagnosis and its managementbecomes difficult. The Acute Kidney Injury Network (AKIN)recommends AKI criteria based on increased serum creatininelevel and reduced urine output.Objectives To identify the prevalence of AKI in asphyxiatedneonates using the AKIN criteria, to compare the difference ofAKI stages, and the glomerular filtration rates (GFR) betweenmoderate and severe asphyxia.Methods This was a cross-sectional analytical study conductedbetween July 2012 and January 2013. Subjects were all asphyxiatedneonates (Apgar score < 7 at fifth minute) with gestational age of>35 weeks delivered and hospitalized in Cipto MangunkusumoHospital and Koja District Hospital, Jakarta, Indonesia.Glomerular filtration rate was calculated using the componentsof urine creatinine, serum creatinine, and urine output; whileAKI stages were determined according to AKIN criteria. Urinaryoutput was measured via urethral catheterization.Results Of 94 subjects, there were 70 neonates with moderateand 24 neonates with severe asphyxia, with the prevalence of AKIwas 63%. Twenty one out of 24 neonates with severe asphyxiaexperienced AKI, while neonates with moderate asphyxia whoexperienced AKI was 38 out of 70 subjects (54%). Two third ofneonates with severe asphyxia who experienced AKI had stage3 of AKI. More severe AKI stages and lower median GFR werefound in neonates with severe compared to moderate asphyxia(P<0.001) .Conclusion The prevalence of AKI in neonatal asphyxia is high(63%). The more severe degree of neonatal asphyxia, the moresevere AKI stage and the lower median GFR.